IMPLEMENTASI KEBIJAKAN RETRIBUSI PARKIR Di KECAMATAN PALU SELATAN KOTA PALU PROVINSI SULAWESI TENGAH - Ahmad firdaus; Irwan waris; Nawawi natsir (JURNAL ILMIAH RESEARCH STUDENT, 2024)
Parking service fees along public roads contribute significantly to the revenue of Palu City. To enhance local revenue, the optimal implementation of policies regarding on-street parking service fees is crucial for the Palu City Transportation Agency. This research employs a qualitative descriptive method, with five purposively selected informants. Data collection methods include observation, interviews, and document analysis. The study utilizes the policy implementation theory developed by Merilee S. Grindle, encompassing policy content and implementation context. The findings reveal suboptimal implementation of the on-street parking service fee policy by the Palu City Transportation Agency. The evaluation is based on two aspects proposed by Merilee S. Grindle, with the policy content aspect deemed less than optimal. Meanwhile, the implementation context aspect is considered to be involved optimally.